CONCEPTS AND SIGNS OF WORK ORGANIZATION AND LABOR RELATIONS - Stadnichenko, Serhiy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: the aim of the article is to study the main aspects of labor organization and employment relations as key elements of modern enterprise management in a market economy. The research is focused on identifying the main characteristics and elements of these concepts, as well as analyzing their impact on the efficiency and sustainability of enterprises. Special attention is given to the legal, social, and economic aspects of employment relations, as well as the challenges arising from the implementation of new labor organization models in various socio-economic conditions. Research methods: a multidisciplinary approach is used, combining economic, legal, and social analysis. Methods of comparative analysis are employed to study various labor organization models adopted in different countries and their adaptation to local conditions. System analysis methods are also applied to examine the interconnection between labor organization and employment relations. The sources used include scientific publications, legal documents, and analytical reviews, allowing for a comprehensive approach to the topic under study. Results: the study revealed that effective labor organization includes a set of measures aimed at the rational use of labor force and production resources, such as labor division, standardization, motivation, and workplace organization. It contributes to the optimization of labor activities, increased productivity, and the achievement of strategic enterprise goals. It is also found that employment relations, as a specific type of legal relationship, are an important factor in ensuring the stability and fairness of the labor process. The analysis of the legal, social, and economic aspects of employment relations highlights their role in maintaining effective management of labor resources. Discussion: the article discusses the main challenges faced by managers when implementing new labor organization models, particularly in adapting foreign methods to local socio-economic conditions. It is determined that considering national characteristics and legislative requirements during the adaptation of methodologies is crucial, as neglecting these factors can lead to ineffective management decisions. The authors conclude that a comprehensive approach to labor management is necessary, which includes both effective organization of labor processes and proper regulation of employment relations to achieve high productivity, employee satisfaction, and sustainable enterprise development in a globalized world.